Planted by the Signs : Poems - Skaggs, Misty, 1982- (Book collections on Project MUSE., 2019)
"Planted by the Signs brings us the contemporary Appalachian poetry of Misty Skaggs. With a knack for pointed personal and social observation, she tells the stories of generations of women who have learned to navigate a harsh world with a little help from the Farmers' Almanac and the stars: women who know how to plant by the signs"--